Performing Tradition and Ethnicity at the Newfoundland St. Andrew’s Society Burns Supper - Fraser, Joy (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
This article explores competing conceptualisations of tradition and ethnicity as they are enacted at an annual celebration of Scottishness in St. John’s, Newfoundland: the Newfoundland St. Andrew’s Society Burns Supper. It begins by discussing the significance attached to notions of maintaining tradition and celebrating ethnicity on the part of the event’s organisers and participants. It goes on to focus in depth on two performances by local poets and entertainers, Christopher and Michael Pickard, invited speakers at the January 2007 event. These performances are shown to encode markedly different attitudes towards tradition and ethnicity to those which underpin the celebration of the Burns Supper as a whole. Analysis of the Pickard brothers’ performances thus affords a valuable opportunity to investigate the tensions which are set into motion when these two competing perspectives confront each other in the context of an organised public event like the Burns Supper. It also helps to illuminate wider issues relating to tradition and ethnicity at play within the discourse of the event.